ISOLATION OF NOVEL PARA-PENTYL PHENYL BENZOATE FROM MONDIA WHITEI.(HOOK.F.) SKEELS (PERIPLOCACEAE), ITS STRUCTURE, SYNTHESIS AND NEUROPHARMACOLOGICAL EVALUATION. - Bamigboye J, Taiwo; Josephine Y, Osasan; Olujide O, Olubiyi; Idris A, Oyemitan; Shakir A.M, Atoyebi; Mark R.J., Elsegood; Raymond C.F, Jones (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Mondia whitei L. (Hook. F.) Skeels (Periplocaceae) is a medicinal plant used locally in managing pain, fever,loss of appetite and as aphrodiasc in the South-Western states of Nigeria. However, the fruit is consumed habitually in theSouth-Eastern states of Nigeria, leading to speculation that it may possess some central nervous system effect but which hasnot been scientifically investigated, hence this study.Methodology: Fresh fruits of Mondia whitei were collected and identified by a taxonomist. They were chopped into smallpieces and extracted with absolute ethanol. The crude extract was subjected to various chromatographic techniques toisolate a novel compound whose structure was elucidated from the analysis of the crystal data and by extensive use ofspectroscopy. The structure was confirmed by synthesis. The compound was subjected to anxiolytic and sedative activityassay. Computational analysis of the receptor binding event of isolated compound at the gamma amino butyric acid Areceptor was also evaluated.Results: The structure of the compound was elucidated as para pentyl phenyl benzoate. The neuropharmacologicalevaluation of the compound indicated significant (p<0.05) depression of the central nervous system. The bindingcharacteristics of the compound to gamma amino butyric acid A receptors appears to be more favorable than those obtainedfor gamma amino butyric acid, chlorpromazine, benzamidine, and is comparable with the affinity obtained forpentobarbitone and diazepam.Conclusion These present data provide evidence for the role of para pentyl phenyl benzoate in the habitual consumption ofthe fruit as well as its central nervous system activities.